Fluorinated caffeic acid phenethyl ester antioxidant with enhanced pharmacological activities: a theoretical study. Issue 1 (2nd January 2021) - Wang, Guangtong; Wu, Xin
ABSTRACT: It has become obvious that fluorinated drugs have a significant role in medicinal applications. In this study, the fluorination of caffeic acid phenethyl ester (CAPE) antioxidant was investigated using density functional theory calculations. We found that the intramolecular hydrogen bonding and charge transfers of the CAPE were influenced by fluorine substitution. Our results reveal that fluorination altered the stability, solubility and molecular polarity of the CAPE. Our calculations show that free energy transfers of fluorinated derivatives of CAPE in water were negative that it meant that the designed molecules dissolving in the aqueous phase occurred simultaneously. We found that fluorination can increase the first hyperpolarizability of the CAPE. Our results present an efficient strategy to improve the nonlinear optical responses of the antioxidants. Consequently, the results of the present study show that the fluorination of CAPE could be considered as a promising strategy to design antioxidants with better pharmacological properties.